Characteristics of self-induced flapping jet from a rectangular nozzle - Yoshihisa KATO; Makoto KANAMORI; Shigeki IMAO; Satoshi KIKUCHI; Yasuaki KOZATO (Nihon Kikai Gakkai ronbunshu, 2014)
Turbulent jets are utilized in various industrial devices such as combustors and ejectors. To control jets and enhance mixing, several devices have been developed, and mixing process also has been studied. For the practical applications, such devices should be simple, reasonable and durable. In this study, a flapping jet is focused for mixing passively. The flapping jet is a self-induced oscillating flow which emerges from a fluidic device. The fluidic device used here is referred to by Mi et al., 2001 and it consists of a slit and a rectangular duct. The objectives of this study are to specify occurring condition of the flapping jet and to clarify the characteristics and the mechanism of it by means of flow visualization and velocity measurement. It is found that the flapping jet occurs depending on the rectangular nozzle dimension, and periodic flapping occurs when the ratio of duct width to slit width is about 1.6 and the ratio of duct height to duct length is 0.4～0.65. It is noticed that flapping frequency depends on the dimension of the duct and Strouhal number is almost constant against Reynolds number, but it decreases with an increase in duct height. It also becomes apparent that the flapping jet spreads widely and the half width becomes about 3 times wider than that of no flapping. In addition, the deflection of flapping jet is revealed to be caused by the vortex in the rectangular duct, which is generated between the main flow and the reverse flow from the outside of the rectangular duct.